Hope you know that x^(-1) = 1/x used this you get
(-5x^3)^-2 = 1/(-5x^3)^2 = 1/{(-5^2)(x^6)} = 1/(25x^6)
hope helped
Answer:
Step-by-step explanation:
(3x^2 + 2x - 3)(x-1)
Expanding the brackets
x(3x^2 +2x - 3) -1(3x^2 +2x -3)
3x^3 +2x^2 -3x -3x^2 -2x + 3
3x^3 - x^2 - 5x + 3
Answer:
<h3>aww thanks </h3>
the process by which plants and animals.make their own food is called photo synthesis.
Answer:8.1000=8000
9.100=900
8000>900
8.1000>9.100
Step-by-step explanation:
B= 2000 + CD
98000 = B + CD
substitute b in
98000 = 2000 + CD + CD
add variables
98000 = 2000 + 2CD
subtract 2000 from each side
96000 = 2CD
divide each side by 2
48000 = CD